Comparative demonstration trials of winter wheat varieties of the ARC “Donskoy” in the zone of blackearth soils of the Volgograd region - V. L. Sapunkov (Зерновое хозяйство России)
The current paper has considered the results of comparative trials of winter wheat varieties of the ARC “Donskoy” in the zone of blackearth soils, the subzone of southern blackearth of the Volgograd region. Modern breeding provides a wide choice of winter wheat varieties. In the Volgograd region, more than 100 varieties are sown annually. This objectively results in difficulty of the best choice. Based on the official data on the preferences of farmers, there have been optimized the selection base, focusing on the varieties of the ARC “Donskoy”, considering it more important and responsible for farmers to clarify information about this significant (about 60 %) block. The field trial was laid in the Kikvidzensky district of the Volgograd region in the zone of blackearth soils, the subzone of southern blackearth, on the lands of “AGROPRODUKT” LLC. The study was carried out according to the methodology used by the State Variety Commission. Significant effect on the autumn stage of development was made by weather conditions, which were significantly contrasting, during the years of trial. The value of field germination was at the level of 65–75 %. The indicators of autumn tillering at the end of the autumn vegetation period for three years were in a rather narrow range of 3.9–4.7 pcs/plant. In the studied area, the formation of yield due to the density of productive stems prevailed. On average, for three years, the value of the productive stalk was 610–729 pieces/m2. According to this indicator, the winter wheat varieties ‘Krasa Dona’, ‘Donskaya Step’, ‘Kapitan’ (679–729 pcs/m2) were the best ones. As a result, the best productivity indicators were demontarted by the varieties ‘Krasa Dona’ (5.66 t/ha) and ‘Donskaya Step’ (5.41 t/ha). A significant group of varieties, such as ‘Kapitan’, ‘Lidiya’, ‘Asket’, ‘Zhavoronok’, formed 5.21– 5.26 t/ha.